Vibration characteristics of the gear shaft-bearing system with compound defects under variable operating conditions. (March 2022) - Dai, Peng; Wang, Jianping; Yan, Shuping; Huang, Shengzhou; Wang, Fengtao; Liu, Jun
Due to the variable working conditions, there are compound defects in the gear shaft-bearing system easily, vibration signals are very complex, and the fault diagnosis of the system becomes more difficult. Thus, a 36 degrees of freedom (36-DOFs) dynamic model is established for discussing the vibration characteristics of the gear shaft-bearing system, the gear pair spalling defect is considered, there are localized defects on the inner raceway and outer raceway of the supporting bearing, the work conditions contain variable speed, variable load, speed fluctuation, and load fluctuation. The obtained vibration signal is processed by the short-time Fourier transform for the time–frequency distribution map. When the gear shaft-bearing system with compound defects operates under variable conditions, roller passing outer raceway frequency, roller passing inner raceway frequency, gearing meshing frequency, and the relative harmonic frequencies can also be found. The defect frequencies and frequency amplitude are increasing with the speed while the system makes the accelerated movement. While the load acting on the system increases, the defect frequencies remain unchanged, but the frequency amplitude becomes larger. If there are fluctuations of the speed and load, the apparent defect frequency fluctuation and amplitude fluctuation is generated. The mathematical model and the analysis results are verified by the experiment, which will provide the theoretical basis for the fault diagnosis of the gear shaft-bearing system.